The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3354/ab00055
|View full text |Cite
|
Sign up to set email alerts
|

Biology of shallow marine ichnology: a modern perspective

Abstract: This study considers the construction and functionality of biogenic structures made by marine, vermiform nemerteans, polychaetes and hemichordates; marine crustaceans; motile bivalves; motile echinoderms; and sponges and sea anemones. We report on a range of modern biogenic structures similar to several known ichnogenera. Vermiform animals dominantly occupy vertical burrows that range from simple through helical shafts to Y-and U-shapes. Horizontal traces made by worms range in form, but are dominated by branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 59 publications
(58 reference statements)
0
44
0
Order By: Relevance
“…The X-radiographs revealed that cup-in-cup structures were produced as the holothurians gradually moved upward in response to sediment aggradation [13]. Field observations of Thyone have shown that they produce irregular U-shaped burrows similar to those of T. gemmata in intertidal settings although these have not been described in detail [16,17]. Laboratory experiments with H. scabra indicated that this species burrowed in response to daylight and decreasing salinity, however, neither the burrowing method nor the burrows were described in this study [4].…”
Section: Other Examples From the Modern And Fossil Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-radiographs revealed that cup-in-cup structures were produced as the holothurians gradually moved upward in response to sediment aggradation [13]. Field observations of Thyone have shown that they produce irregular U-shaped burrows similar to those of T. gemmata in intertidal settings although these have not been described in detail [16,17]. Laboratory experiments with H. scabra indicated that this species burrowed in response to daylight and decreasing salinity, however, neither the burrowing method nor the burrows were described in this study [4].…”
Section: Other Examples From the Modern And Fossil Recordmentioning
confidence: 99%
“…The extant holothurians Thyone briareus [5,[13][14][15][16][17], Holothuria scabra [4], and Protankyra bidentata [18] are three exceptions. Pearse [5] conducted various experiments with T. briareus including some designed to observe the animals burrowing methods.…”
Section: Other Examples From the Modern And Fossil Recordmentioning
confidence: 99%
“…Their results show that we can be fairly confident about the origin of some trace fossils, but also that similar structures can be produced by different taxa behaving in very different ways. Traces morphologically equivalent to the ichnogenus Gyrolithes, for example, are produced by worms anchoring themselves to the seabed, and by ramp-building shrimps (Gingras et al 2008). This highlights the risk of interpreting trace fossils definitively, but further studies of this kind can provide greater clarity.…”
Section: Bioturbation and Behaviourmentioning
confidence: 99%
“…Most of these invertebrates actively rework the sediment, a process that may disturb the natural deposited stratification, facilitate the horizontal movement of particles, and restyle the microtopography of the sediment (Gerino et al, 2003;Gingras et al, 2008;Maire et al, 2008). Indeed, to respire, feed, and excrete metabolites, benthic invertebrates must renew their burrow water through bioirrigation (Kristensen and Kostka, 2005).…”
Section: Introductionmentioning
confidence: 99%